The challenging path to a redistribution of space - renegotiating urban mobility. - Wendorf, Gabriele; Schröder, Carolin (My University, 2018)
The (rapid) growth of cities and city populations in many regions of the world puts a focus on the question of accessibility (use and distribution) of urban space. In consequence, the long-prevailing hegemony of the principle of car-friendly cities is being challenged, and political as well as societal mindsets towards individually possessed cars seem to be changing. Nonetheless, more sustainable forms of mobility will need different legal and economic frameworks, and will need to be more demand-orientated and smarter in order to become a real alternative. From a technological perspective, new regulations on the reduction of (CO2), NOx and particulate matter have been passed by the European Parliament in 2015, while smart forms of mobility such as carsharing, e-mobility, and automated driving are being supported and subsidized by local and national governments. Both, regulations and incentives from the market are pushing companies to innovate. From a socio-political perspective, the (re-)distribution of the increasingly scarce resource urban space and the manner of its utilization is a challenge which affects all population groups, but in different ways. Questions arising in this context are: How to actually initiate a process of transformation towards a more sustainable urban mobility? What future quality(s) of life will we have in demographically changing societies and which forms of mobility are more adequate to future needs than individual possession of cars? This is exactly where our transdisciplinary project in Berlin/Germany takes off: place-based approaches promoting more sustainable forms of local mobility are being combined with iterative bottom-up approaches of discussion, information and playful testing of new forms of mobility for civil society, stakeholders, administrators and politicians. One and a half year into the project, it becomes obvious that urban mobility is a highly contested and emotionalized topic where fear of loss (of the individually possessed car and its parking space) clashes with misinformation, non-reflection of individual mobility behavior and demand, and different esthetic preferences on how public space should be designed. This contribution presents intermediary results from a research project in Berlin/ Germany (http://neue-mobilitaet.berlin/) where local actors together with administrators, politicians, mobility providers and researchers are about to develop and test adequate strategies towards more sustainable local mobility. These intermediary results can be summarized as follows: 1) In order to develop a truly different, and less emotional approach to (sustainable) mobility, intensive communication with different groups and across these groups is necessary. 2) Smartness in the mobility sector is not merely the introduction of innovative technology-based solutions but needs to be understood as a process of multilateral information, discussion, and exchange.
Keywords: Stadtraum; Raumnutzung; Verkehrsraum; Nutzungskonflikt; Nachhaltige Mobilität; Mobilitätskonzept; Verkehrsmittelwahl; Verhaltensänderung; Kommunikation